A novel small punch creep test to determine norton creep properties of LPBF Ti64 alloy - Shi, Furui; Lalé, Mathieu; Yu, Feng; Abendroth, Martin; Viguier, Bernard; Li, Yingzhi (Frontiers in Materials, 2025)
Laser Powder Bed Fusion (LPBF) Ti-6Al-4V (Ti64)alloy is increasingly favored in additive manufacturing (AM) for complex, lightweight, and high-strength components. However, the inherent microstructural heterogeneity in LPBF materials necessitates specialized characterization methods to ensure reliable performance in service conditions. The Small Punch Creep Test (SPCT) has gained recognition as an innovative and efficient technique for assessing materials creep behavior, particularly beneficial for AM components allowing easier sampling and local characterization of microstructure heterogeneities. Although standards such as CWA 15627 and EN 10371 provide empirical correlations between SPCT and uniaxial creep test (UCT) results, the complex deformation mechanisms in LPBF materials, including anisotropy, porosity, and phase evolution, necessitate material-specific calibration for accurate interpretation. This study proposes a direct methodology to derive the Norton creep parameters of LPBF Ti64 alloy from both Small Punch Test (SPT) and SPCT data, integrating a new representative stress-strain method with inverse finite element analysis (FEA). By first extracting elasto-plastic properties from SPT using the representative stress-strain method, the model enables efficient extraction of Norton creep parameters through inverse analysis of SPCT results. Experimental validation on LPBF Ti64 alloy demonstrates strong agreement with properties derived from SPCT, verifying the accuracy and practical applicability of the proposed method for AM components.